THE PREDICTING FACTORS AFFECTING THE OCCURRENCE OF STUNTING IN CHILDREN UNDER FIVE YEARS OF AGE (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2015)
Stunting adalah salah satu masalah kesehatan utama yang berkaitan dengan nutrisi di seluruh dunia, khususnya negara-negara berkembang. Tujuan dari penelitian ini adalah untuk mengetahui faktor utama yang mempengarui terjadinya stunting pada anak usia dibawah lima tahun. Penelitian ini dilakukan pada tahun 2014 dan merupakan penelitian descriptive cross-sectional. Teknik pengambilan sampel yang digunakan adalah purposive sampling untuk memilih posyandu, dan untuk menentukan sampel pada masing-masing posyandu menggunakan proportion stratified random sampling. Total sampel yang digunakan sebanyak 181 sample. Chi-square test and Logistic regression digunakan untuk menganalisis data. Hasil penelitian menunjukan hubungan yang signifikan antara pendek dengan berat badan lahir (nilai p .001, PR =1.83), pendidikan ibu (nilai p =.009 PR = 1.80), pengetahuan ibu tentang malnutrisi (nilai p .001, PR= 2.28), dan tipe-tipe keluarga (nilai p= .003, PR= 1.64); faktor utama penyebab anak pendek pada anak usia dibawah lima tahun adalah pengetahuan ibu tentang malnutrisi (p-value= 0.01, Exp(B)= 0.35).Stunting is one of the main nutritional health problems throughout the world, particularly in developing countries. The objective of this study was to examine the predictor factors affecting the occurrence of stunting in children under five years of age. This research was conducted at 2014 and this was a descriptive cross-sectional study. The purposive sampling technique was used to choose the community health meeting, and the proportion stratified random sampling technique was used to selecting the sample in each community health meeting. The total sample size was 181 samples. Chi-square test and Logistic regression were used to analyze the data. The results showed the significant relationships between child’s birth weight (p-value .001, PR =1.83), mother’s education (p-value =.009 PR = 1.80), mother’s knowledge of child malnutrition (p-value .001, PR= 2.28), and family types (p-value= .003, PR= 1.64) with stunting; The predictor factor of stunting in children under five years of age was mother’s knowledge of child malnutrition (p-value= 0.01, Exp(B)= 0.35).